Behind the veil voices of moro women - Rimban, Luz; Bonoan, Jam; Maglipon, Jo-Ann; Diokno, Ma. Socorro (The Center, 1998)
A documentary on the dilemma faced by the Bangsamoro women. War is bloody and costly. And peace does not always right old wrongs. Through these uncertainties, the anchor that keeps the Bangsamoro woman strong is her religion. The veil is her commitment to Islam and symbolizes submission to the teaching of Koran.